National Big Data Experimental Area and the Unexpected Booming of the Housing Price in Guiyang of Guizhou Province of China - Lu Zhang; Hongfei Yu; Zhongfa Zhou; Fangxin Yi; Dong Li (Land, 2023)
Enterprise Zone is an important part of the regional economic development strategy. This paper investigates the impact of overall urban development and construction of the National Big Data (Guizhou) Experimental Area on the housing prices and found out that the construction of the National Big Data (Guizhou) Experimental Area is more conducive to the rise in suburban housing transaction prices. The paper empirically proves that the construction of the National Experimental Zone is more conducive to small family housing and leads to the increase in the suburban housing trading area, which further implies that the National Big Data (Guizhou) Experimental Area project may lead to the migration of residents to the suburbs, thus the increasing the housing price. Such regional planning is conducive to the changing spatial distribution of the residents, relocating the residents to find jobs and live in the suburbs, and increasing the value of suburban areas. This paper provides evidence to quantify the externalities and the premium of the housing prices in the surrounding area and provides empirical evidence on the spatial externalities in the literature.